2020
DOI: 10.1177/0269215520942953
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of pulsed ultrasound treatment on pain, function, synovial sac thickness and femoral cartilage thickness in patients with knee osteoarthritis: a randomized, double-blind clinical, controlled study

Abstract: Objective: This study aims to investigate the efficacy of therapeutic pulsed ultrasound on pain, function, synovial sac and femoral cartilage in knee osteoarthritis. Design: Randomized, double-blind, controlled study Setting: Dokuz Eylul University, Department of Physical Medicine and Rehabilitation Subjects: A total of 96 patients with knee osteoarthritis Interventions: Participants were randomized into two groups; Group I ( n = 48, pulsed ultrasound) and Group II ( n = 48, sham ultrasound). The sessions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…After the whole selection process, 37 articles were included in the systematic review, of which 13 studies with 807 subjects were included in the meta-analysis for statistical comparison. [29][30][31][32][33][34][35][36][37][38][39][40][41] The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the whole selection process, 37 articles were included in the systematic review, of which 13 studies with 807 subjects were included in the meta-analysis for statistical comparison. [29][30][31][32][33][34][35][36][37][38][39][40][41] The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…31,32,35 And ten studies used it as a combination therapy. 29,30,33,34,[36][37][38][39][40][41] The outcome indicators of the included studies were: the Visual analog scale score, the Western Ontario and McMaster Universities Osteoarthritis Index score, the Lysholm score, the Lequesne index, Range of motion, 20 meters and 50 meters walking time. The follow-up period ranged from 2 weeks to 1 year.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine trials using continuous ultrasound as a treatment, eight reduced WOMAC scores by 20%. While most studies showed favorable relative risk reductions in WOMAC, only a few studies [ 55 , 56 , 57 ] yielded clinically significant relative risk reductions in stiffness WOMAC score, with −62.5%, the relative risk reduction for pain WOMAC score being the most clinically significant [ 57 ]. Discrepancies in findings can be attributed to the combination of ultrasound application with or without rigorous exercise.…”
Section: Physical Therapy Interventionsmentioning
confidence: 99%